2009
DOI: 10.1007/s00221-008-1695-z
|View full text |Cite
|
Sign up to set email alerts
|

Velocity control in Parkinson’s disease: a quantitative analysis of isochrony in scribbling movements

Abstract: An experiment was conducted to contrast the motor performance of three groups (N = 20) of participants: (1) patients with confirmed Parkinson Disease (PD) diagnose; (2) age-matched controls; (3) young adults. The task consisted of scribbling freely for 10 s within circular frames of different sizes. Comparison among groups focused on the relation between the figural elements of the trace (overall size and trace length) and the velocity of the drawing movements. Results were analysed within the framework of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 109 publications
0
16
0
2
Order By: Relevance
“…As the differences between patients and controls were not restricted to a certain path nor a certain speed, they were probably not due to abnormalities in spatial perception nor to the geometry of the elliptical paths [57], [58]. Rather, these differences appear to represent a more global deficit in how visual motion is perceived in PD.…”
Section: Discussionmentioning
confidence: 85%
“…As the differences between patients and controls were not restricted to a certain path nor a certain speed, they were probably not due to abnormalities in spatial perception nor to the geometry of the elliptical paths [57], [58]. Rather, these differences appear to represent a more global deficit in how visual motion is perceived in PD.…”
Section: Discussionmentioning
confidence: 85%
“…As mentioned in the Introduction, changes in hand function are among the relatively early symptoms of PD (McLennan et al 1972; Viviani et al 2009). Our previous studies showed significant changes in multi-finger synergy indices and ASAs during pressing tasks even in patients at stage-I PD (Park et al 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although hand motor dysfunction is a well-documented early consequence of Parkinson’s disease (PD, e.g., micrographia, McLennan et al 1972; Viviani et al 2009), problems with finger coordination are not mentioned among the cardinal signs of PD. A series of recent studies in patients with early-stage PD documented changes in finger interaction and coordination indices during isometric force production tasks (Park et al 2012, 2013a, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One important feature of programmed motor behavior is the principle of isochrony, which refers to the relationship between distance and velocity of hand movements during limb movement. Isochrony stipulates that the average velocity of endpoint movement increases with movement distance (hence preserving the time span, making it isochronous ), and is present in many if not most types of movement (Viviani et al, 2009; Viviani and Flash, 1995). For example, when moving the elbow to different degrees of flexion, normal healthy individuals will scale movement velocity in proportion to degrees of flexion, thus maintaining a constant movement time.…”
Section: Methodsmentioning
confidence: 99%